AESTHETIC-COMPLEX ENVIRONMENTAL THOUGHT THROUGH CINEMA AS A MEDIATOR (2015)
This process of Educational Research aims to build Aesthetic-Complex Environmental Thinking within the B.S. Program in Biology and Environmental Education at the University of Quindío, from generating scenarios of interpretation of some films, in order to think critically and reflexively about development models, ways of inhabiting the land, and the biodiversity crisis. The methodology consisted of selection, projection and analysis of films with their respective literary support or script, namely: Akira Kurosawa's “Dreams,” Luis Buñuel's “The Forgotten Ones,” Antonio Dorado's “Apaporis In Search of One River,” Charlie Chaplin's “Modern Times” and “The Gold Rush”, Carlos César Arbelaez's “The Colors of The Mountain,” Jairo Carrillo's “Small Voices,” José Luis Cuerda's “Butterfly,” and Disneynature's “Earth.”From these academic scenes stories of participants emerge, from which in turn trends of thought are constructed, in the manner of statements, such as: an anthropocentric view of the world as an inheritance of modern thought, the monstrosity within the thinking about relations with nature, the crisis of science as a civilizing crisis, the devastation of nature and culture as a crisis of meaning in life, and rethinking the ways of inhabiting, as keys of resistance against intemperate growth/progress. These statements and their written elaboration are performed taking into account authors in the field of contemporary environmental thought and expert writers on film appreciation and analysis, and are considered findings or conclusions, entitled in this work as investigative emergencies.